2019
DOI: 10.1021/acsami.9b10444
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin-Loaded Thermoresponsive Superparamagnetic Nanocarriers for Controlled Drug Delivery and Magnetic Hyperthermia Applications

Abstract: This study reports on the development of thermoresponsive core/shell magnetic nanoparticles (MNPs) based on an iron oxide core and a thermoresponsive copolymer shell composed of 2-(2-methoxy)­ethyl methacrylate (MEO2MA) and oligo­(ethylene glycol)­methacrylate (OEGMA) moieties. These smart nano-objects combine the magnetic properties of the core and the drug carrier properties of the polymeric shell. Loading the anticancer drug doxorubicin (DOX) in the thermoresponsive MNPs via supramolecular interactions prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 52 publications
(104 reference statements)
2
57
0
Order By: Relevance
“…In addition, the theragnostic approach also includes using the SPIONs properties to destroy proliferating cells, by hyperthermia-mediated drug delivery [112], or in combination with optical probes able induce photothermal effects when combined with heptamethine cyanine [109], treating tumors in mice by photodynamic therapy using Chlorine e6 or Dextran Benzoporphyrin coating SPIONs, reported in [113] and [114], respectively.…”
Section: Further Outlookmentioning
confidence: 99%
“…In addition, the theragnostic approach also includes using the SPIONs properties to destroy proliferating cells, by hyperthermia-mediated drug delivery [112], or in combination with optical probes able induce photothermal effects when combined with heptamethine cyanine [109], treating tumors in mice by photodynamic therapy using Chlorine e6 or Dextran Benzoporphyrin coating SPIONs, reported in [113] and [114], respectively.…”
Section: Further Outlookmentioning
confidence: 99%
“…For example, Liu et al employed SPIONs to accurately delivery DOX‐loaded MSNs to tumor site with minimal toxicity to healthy tissues in the guidance of magnetic field (Figure 12A). 270 Besides, a SPIONs‐based core‐shell nanostructure loading DOX into the thermoresponsive copolymer shell was successfully established 271 . They found that the DOX cumulative release percent from this nanostructure incubated at 37°C was almost 0% after 10 h, while the release amount encouragingly reached to 100% at 42°C after 54 h. It is interesting to note that the increased temperature of SPIONs, possessing magnetic hyperthermia effect, was high enough (>42°C) to initial burst release of DOX under magnetic stimulation.…”
Section: Exogenous‐triggered Smart Materialsmentioning
confidence: 99%
“…Antibiotics, growth factors, and microRNA and siRNA related to osteogenesis can improve the repair effect of bone defects (Jia et al, 2018 ; Li et al, 2018 ; Ferjaoui et al, 2019 ). However, these drugs cannot target specific sites or produce a direct repair effect.…”
Section: Preparation Of Magnetic Nanomaterialsmentioning
confidence: 99%